FORMATION AND DEVELOPMENT OF COMPUTER GRAPHICS IN GEODESY - Разум, Руслан; Ветровой, Андрей; Свекла, Николай (SWorldJournal, 2020)
The paper presents the main stages of computer graphics in geodesy and its current state. An analysis of the tasks facing computer graphics and prospects for the development of computer graphics in geodesy.